ASEAN and human trafficking : case studies of Cambodia, Thailand and Vietnam - Kranrattanasuit, Naparat (International studies in human rights., 2014)
Trafficking in persons is a serious crime that affects the human rights, dignity and integrity of all its victims including women, men, and children in the Association of Southeast Asia Nation (ASEAN) region. ASEAN has made efforts to fight human trafficking through inter alia the establishment of regional counter-human trafficking laws and human rights bodies to establish best norms and practices for its member countries. Nevertheless, the International Labour Organization (ILO) recently declared that there are more than 11.7 million forced labor victims in the Asia-Pacific region enc.